Regioselictivity in styrene oxide epoxide cycle cleavage by ethylenediamines in different solvents - A. H. Mohammed; E. Ya. Borisova; V. V. Egorova; A. V. Krylov; N. Yu. Borisova (Тонкие химические технологии)
The results of styrene oxide epoxide cycle cleavage by diamines were summarized. The effect of solvent on regioselectivity in the reaction of N,N-diethylene diamine was studied. It was established that the ratio of products correlates well with polarity parameters ЕТ and АN of pure solvents.